Üniversiteli öğrencilerinin çevre duyarlılıklarının incelenmesi - Burcu ÇABUK; Cem KARACAOLU Ö. (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
This research was conducted among 439 students with the aim of identifying the ideas of the students in the Faculty of Educational Sciences in Ankara University about environmental sensitivity. In this study, the differences between the personal characteristics of these students, such as gender, age, department and class that he/she attended and their environmental sensitivity were examined. In the research, a questionnaire has a 24 guestion which was developed by reviewing the literature was used. The environmental sensitivity of the students and the ideas of the university students about the sufficiency of the environmental education in organized education were determined using this questionnaire. The study of validity and reliability of the questionnaire was performed and SPSS was used in the analysis of the data. According to the students' opinions, the fact that sufficient education as to air, water and soil pollution in organized (formal) educational associations is not given and that there are differences among the students' environmental awareness have taken place in the results of the research